2022
DOI: 10.1002/cam4.4796
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structures in lung adenocarcinoma: characteristics and related factors

Abstract: Objective Tertiary lymphoid structures (TLSs) are found in a variety of malignancies and affect the growth of tumors, but few studies have addressed their role in lung adenocarcinoma (LAC). We aimed to evaluate clinical features associated with TLSs in patients with LAC. Methods and Materials A collection of resected pulmonary nodules in patients with LAC was retrospectively analyzed. TLSs were quantified by their number per square millimeter tumor area (density) and by the degree of lymphocyte aggregation (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In cancer research, where the TME plays an important role in dictating therapy responses, the ability offered by hoodscanR to identify neighborhoods offers a unique perspective to investigate novel mechanisms underlying the transition of cancer cells at both transcriptomic and proteomic level. Notably, our findings from the NanoString CosMx NSCLC dataset identified cellular neighborhoods that potentially associated with the presence of TLS, which correlated with positive clinical results 11 . This capability offers the potential to contribute valuable insights into the progression of cancer, paving the way for the development of novel therapeutic strategies.…”
Section: Hoodscanr Identifies Celluar Neighborhoods In Cancermentioning
confidence: 54%
See 1 more Smart Citation
“…In cancer research, where the TME plays an important role in dictating therapy responses, the ability offered by hoodscanR to identify neighborhoods offers a unique perspective to investigate novel mechanisms underlying the transition of cancer cells at both transcriptomic and proteomic level. Notably, our findings from the NanoString CosMx NSCLC dataset identified cellular neighborhoods that potentially associated with the presence of TLS, which correlated with positive clinical results 11 . This capability offers the potential to contribute valuable insights into the progression of cancer, paving the way for the development of novel therapeutic strategies.…”
Section: Hoodscanr Identifies Celluar Neighborhoods In Cancermentioning
confidence: 54%
“…B cell neighborhoods serve as crucial sites for antibody production, contributing to the immune response against tumor cells and influencing therapeutic efficacy 10 . Furthermore, in lung cancer, the presence of tertiary lymphoid structures (TLS), characterized by highly organized T and B lymphocyte colonies within nonlymphoid tissues, has been associated with favorable clinical outcomes in non-small cell lung cancer (NSCLC) 11 . These structures, resembling secondary lymphoid organs, play an important role in regulating antitumor immune responses and are emerging as potential targets for novel therapeutic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have examined TLS maturity in LUAD. Ren et al found that TLS maturity was higher in patients with higher tumor stages [ 22 ]. Wakasu et al suggested that mature TLSs may support antitumor immunity through lymphocyte activation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was first noted in our study that punctate consolidation may be a pathological tertiary lymphoid structure. Tertiary lymphoid structures are clusters of lymphocyte aggregates in non-lymphatic tissues [20,21] and have been shown to participate in the antitumor immune process. Patients with tertiary lymphoid structures have been reported to benefit from long-term survival [22][23][24].…”
Section: Discussionmentioning
confidence: 99%